Estymacja podstawowych funkcji Modelu Coxa - na podstawie wyników leczenia chorób nowotworowych - Król, Piotr (Estimation of Сох Model Based on the Results of Malignant Tumours Therapy, 2007)
The paper discusses the proportional hazard model by Cox describing the phenomena in which the unexpected events (e.g. deaths) exist in the disjoint time intervals. Kalbfleische-Prentice estimators have been to conformed such a model variation, which determines the baseline hazard function h0(t) and the baseline survivals function S0(t). In practice it enables to determine the survival Sx(t) and hazard h(х; t) functions for the researched units varied with the vector of endo- and exogenous features. The discussed functions have been estimated on the medical examples that include patients suffering from malignant tumours. The influence of demographical, social, and economic features on the therapy results has been discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 147-174